Preparation method of cerium-doped tin oxide electron transport layer and application of cerium-doped tin oxide electron transport layer in perovskite solar cell
By doping cerium in the tin oxide electron transport layer, surface defects are suppressed and energy level matching is improved, the interfacial defect state and ultraviolet stability problems in perovskite solar cells are solved, and the photoelectric conversion efficiency and UV resistance are significantly improved.
Patent Information
- Application Number
- CN202411496789.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-24
AI Technical Summary
In perovskite solar cells, there are many surface defects in the tin oxide electron transport layer, which leads to a high-density defect state that spontaneously occurs in the interface with the perovskite layer, affecting carrier extraction and transmission, and long-term ultraviolet light irradiation leads to the decomposition of perovskite materials. , reduce device stability.
By using a cerium-containing tin oxide precursor solution, depositing and annealing under constant temperature conditions through chemical bath method, a cerium-doped tin oxide electron transport layer was prepared, which inhibited the formation of defects such as oxygen vacancies, and improved the perovskite layer and The energy level arrangement of the electron transport layer enhances ultraviolet resistance.
It significantly reduces the oxygen vacancies and tin gap defects in the electron transport layer, improves the photoelectric conversion efficiency and UV resistance of perovskite solar cells, and enhances the stability and durability of the device.
Smart Images

Figure CN119421626A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optoelectronic materials and devices, and in particular to a method for preparing a cerium-doped tin oxide electron transport layer and application of the layer in a perovskite solar cell. Background Art
[0002] As traditional fossil energy continues to be depleted, energy crises and environmental problems are becoming increasingly prominent. As a new generation of clean energy, solar energy has the advantages of abundant reserves, green and clean, economical and convenient, and is considered to be one of the most promising forms of renewable energy. Among them, perovskite solar cells have attracted much attention due to their high performance and low cost. As a representative of the third generation of solar cells, perovskite solar cells (PSCs) have a photoelectric conversion efficiency of 26.7%, which is almost comparable to commercial crystalline silicon solar cells. In addition, due to its advantages such as abundant raw materials, low-temperature liquid phase preparation and low processing cost, perovskite solar cells have become a hot spot for research and application in the photovoltaic field.
[0003] The typical planar perovskite solar cell device structure includes an electron transport layer (ETL), a perovskite light absorbing layer, a hole transport layer (HTL) and an electrode layer. Among them, the electron transport layer (ETL) plays a vital role in extracting and transporting photogenerated electrons, blocking holes and reducing carrier recombination at the interface. Chinese patent CN202010283071.2 discloses an inorganic inverted perovskite solar cell, its preparation method and application, which uses low-temperature cerium oxide as an electron transport layer material, which not only satisfies the requirement of being able to use a low-temperature treatment process, effectively preventing the damage of the perovskite photosensitive layer by high-temperature annealing, but also can be dispersed using a solvent that does not damage the perovskite photosensitive layer, thereby successfully preparing an efficient and stable all-inorganic inverted perovskite solar cell. However, the main problem with this patent is that it does not take into account the problem that the charge recombination phenomenon at the interface is significant due to the large number of interface defects between the perovskite photosensitive layer and the electron transport layer. The neodymium-doped titanium oxide prepared by Liu's team and others improved the injection and extraction efficiency of photoelectrons, exhibited higher conductivity and electron mobility, and lower trap state density. The final device achieved a photoelectric conversion efficiency of more than 19% and had better light stability, but this method did not improve the ultraviolet stability of the device.
[0004] Tin oxide is the best electron transport layer (ETL) material in planar perovskite solar cells (PSCs) due to its wide band gap, high electron mobility, good chemical stability, low photocatalytic activity, and low-temperature preparation. However, there are oxygen vacancies (V O )、Tin gap (Sn i) and other inherent defects lead to the spontaneous formation of high-density defect states at the interface of the electron transport layer / perovskite layer, resulting in serious charge recombination at the interface, affecting the extraction and transmission of carriers, thereby seriously restricting the photoelectric conversion efficiency of the device. In addition, long-term ultraviolet light irradiation can cause photochemical reactions in perovskite materials, causing them to decompose or change their structure. This change not only destroys the crystal structure of the material, but also increases the interface defects between the perovskite layer and the electron transport layer, thereby adversely affecting the long-term stability of perovskite solar cells. Therefore, the preparation of high-performance tin oxide electron transport layers and perovskite solar cells with excellent UV resistance has become a key challenge in promoting the industrialization of perovskite solar cells. These technological breakthroughs can not only significantly improve the overall performance of the battery, but also enhance its stability and durability in practical applications, thereby laying a solid foundation for the widespread promotion of perovskite solar cells. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a cerium-doped tin oxide electron transport layer and its application in a perovskite solar cell. The high-performance tin oxide electron transport layer is prepared by using a cerium salt-containing tin oxide precursor solution, which can reduce the oxygen vacancies (V O ) and tin gap (Sn i ) and other defects; in addition, it can also solve the three main problems faced when using tin oxide as an electron transport layer: First, there are many defects on the surface of tin oxide, which makes it easy for it to spontaneously generate high-density defect states at the contact interface with the perovskite layer; second, the quality of the tin oxide film is poor, and the crystallinity of the perovskite light-absorbing layer is affected when it grows on its surface, resulting in a smaller grain size; third, the problem of decomposition or structural changes of the perovskite material caused by long-term ultraviolet light exposure is solved.
[0006] To achieve the above object, the present invention provides a method for preparing a cerium-doped tin oxide electron transport layer, which comprises depositing a precursor solution containing a cerium salt by a chemical bath method under constant temperature conditions, and then annealing the solution to prepare the cerium-doped tin oxide electron transport layer, comprising the following steps:
[0007] S1, cleaning and drying the FTO substrate, and subjecting the surface of the FTO substrate to UV-ozone treatment for 5 to 20 minutes or plasma cleaning treatment for 1 to 5 minutes;
[0008] S2, measuring deionized water and freezing it to form an ice-water mixture, and then slowly adding urea, concentrated hydrochloric acid, thioglycolic acid and stannous chloride dihydrate to the ice-water mixture in sequence, and stirring until completely dissolved to obtain a tin oxide precursor solution;
[0009] S3, weighing a cerium salt and adding it to the tin oxide precursor solution obtained in S2 to obtain a tin oxide precursor solution containing a cerium salt;
[0010] S4, immersing the FTO substrate treated by S1 into the tin oxide precursor solution containing cerium salt in S3, and depositing it under constant temperature conditions by a chemical bath method. After the deposition is completed, the substrate is taken out, and ultrasonic cleaning, drying, and annealing are performed in sequence to obtain a cerium-doped electron transport layer.
[0011] Preferably, in S2, the pH of the tin oxide precursor solution is 0.5-2.0, and the dosage of each component is 6.250-25.000 g / L of urea, 6.250-25.000 mL / L of concentrated hydrochloric acid, 125-500 μL / L of thioglycolic acid, and 1.375-5.500 g / L of stannous chloride dihydrate.
[0012] Preferably, in S3, the cerium salt is a combination of one or more cerium salts selected from cerium chloride, cerium phosphate, cerium nitrate and cerium acetate; and the concentration ratio of cerium ions to tin ions in the tin oxide precursor solution containing the cerium salt is 1% to 10%.
[0013] Preferably, in S4, the deposition temperature is 80-100° C., and the reaction time is 1-5 h;
[0014] Preferably, in S4, the ultrasonic cleaning solution is one of ethanol, isopropanol, ethylene glycol, and propylene glycol, the ultrasonic cleaning time is 2 to 10 minutes, the annealing temperature is 140 to 200° C., the annealing time is 30 to 90 minutes, and the thickness of the cerium-doped electron transport layer is 10 to 100 nm.
[0015] Preferably, if a thicker tin oxide film needs to be prepared, the substrate surface after drying in step S4 is subjected to UV-ozone treatment for 15 minutes or plasma cleaning treatment for 3 minutes, and then step S4 is repeated again to obtain a thicker cerium-doped electron transport layer.
[0016] An application of a cerium-doped tin oxide electron transport layer. The cerium-doped tin oxide electron transport layer prepared by the preparation method is applied to an organic-inorganic hybrid normal perovskite solar cell.
[0017] Preferably, the method for preparing the organic-inorganic hybrid normal perovskite solar cell comprises the following steps:
[0018] T1. Prepare a cerium-doped tin oxide electron transport layer on the surface of the FTO substrate and treat it with UV-ozone for 15 minutes or plasma cleaning for 3 minutes;
[0019] T2. Preparing a perovskite light-absorbing layer of APbX3 structure on the surface of the cerium-doped tin oxide electron transport layer, wherein A is one or more of methylammonium, formamidine, cesium ion, and potassium ion, and X is one or more of I, Br, and Cl;
[0020] T3, directly preparing the hole transport layer on the surface of the perovskite light absorbing layer by spin coating;
[0021] T4. Prepare an electrode layer on the surface of the hole transport layer by thermal evaporation or magnetron sputtering.
[0022] Preferably, the material of the hole transport layer in T3 is 2,2',7,7'-tetrakis(4-methoxydiphenylamine)-9,9'-spirofluorene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], nickel oxide, copper thiocyanate or copper iodide.
[0023] Preferably, the electrode layer in T4 is one or more of gold, silver, copper, indium tin oxide, and aluminum-doped zinc oxide, and the electrode thickness is 50 to 300 nm.
[0024] Mechanism of the present invention:
[0025] The present invention uses cerium salt to dope the tin oxide electron transport layer. During the doping process, cerium ions interact with the lattice structure of tin oxide, inhibiting the formation of defects such as oxygen vacancies on the surface of the tin oxide electron transport layer, improving the energy level arrangement between tin oxide and the perovskite layer, and reducing the electron transport barrier. In addition, the electron transport layer can not only effectively inhibit the generation of active oxygen species under ultraviolet light irradiation, but also enhance the absorption capacity of ultraviolet light. Under the combined action of this dual mechanism, it helps to reduce the direct damage of ultraviolet light to the perovskite layer, thereby significantly improving the ultraviolet stability of perovskite solar cells. At the same time, cerium doping can also effectively regulate the crystallization of tin oxide, making the electron transport layer flat and dense, thereby promoting the perovskite to obtain a larger grain size and less defective perovskite light-absorbing layer when the perovskite grows on its surface. This will effectively reduce the loss of photogenerated carriers and significantly improve the photoelectric conversion efficiency and anti-ultraviolet performance of perovskite solar cells.
[0026] Compared with the prior art, the present invention has the following advantages and technical effects:
[0027] (1) Effectively suppress oxygen vacancies and tin gaps in the electron transport layer: The present invention discloses a cerium-doped electron transport layer, which uses cerium salts to perform in-situ lattice doping on tin oxide. Cerium ions are embedded in the tin oxide lattice and interact with its structure, thereby suppressing the generation of surface defects such as oxygen vacancies, significantly reducing the non-radiative recombination rate of carriers at the interface of the perovskite battery, and improving the extraction and transmission efficiency of carriers.
[0028] (2) Reduce the density of interface defect states and improve the crystallinity of perovskite film: The cerium-doped electron transport layer of the present invention forms a good energy level match with the perovskite light absorption layer. At the same time, the upward shift of the conduction band top position of the cerium-doped tin oxide electron transport layer reduces the energy barrier of carriers at the interface and optimizes the extraction and transport behavior of carriers at the interface; in addition, it also promotes the conformal growth of the tin oxide electron transport layer on the surface of the FTO substrate, making its surface smoother, improving the wettability of the electron transport layer, and facilitating the epitaxial growth of the perovskite light absorption layer on its surface, generating a light absorption layer with larger grains and fewer defects, thereby significantly improving the photoelectric conversion efficiency of the device.
[0029] (3) Improving UV stability: Since cerium salt is in-situ lattice doped with tin oxide, the electron transport layer has good UV resistance, effectively reducing the direct damage of ultraviolet light to the perovskite material, thereby improving the UV stability of the perovskite solar cell; in addition, the preparation method of the UV-resistant electron transport layer provided by the present invention is simple, low-cost, highly repeatable, highly scalable, and can be mass-produced, which helps promote the commercial application of perovskite solar cells.
[0030] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the structure of an upright perovskite solar cell containing a cerium-doped tin oxide electron transport layer according to the present invention;
[0032] Figure 2 is a JV curve diagram of a perovskite solar cell based on a cerium-doped tin oxide electron transport layer under AM 1.5G test conditions in Example 1 of the present invention;
[0033] Figure 3 is a JV curve diagram of a perovskite solar cell based on a cerium-doped tin oxide electron transport layer under AM 1.5G test conditions in Example 2 of the present invention;
[0034] Figure 4 is a JV curve diagram of a perovskite solar cell based on a cerium-doped tin oxide electron transport layer under AM 1.5G test conditions in Example 3 of the present invention;
[0035] Figure 5 is a JV curve diagram of a perovskite solar cell based on a tin oxide electron transport layer without cerium doping in Comparative Example 1 of the present invention under AM 1.5G test conditions;
[0036] Figure 6 Schematic diagram of JV curve comparison of the perovskite solar cells in Comparative Example 1 and Example 2 of the present invention under AM 1.5G test conditions;
[0037] Figure 7 is a high-resolution energy spectrum of the tin oxide electron transport layer O1s prepared in Comparative Example 1 and Example 2 of the present invention;
[0038] Figure 8 It is a high-resolution energy spectrum of the tin oxide electron transport layer Ce3d prepared in Comparative Example 1 and Example 2 of the present invention;
[0039] Fig. 9 is a SEM image of the cross section of the tin oxide electron transport layer prepared in Comparative Example 1 and Example 2 of the present invention, wherein: Fig. 9 (a) is the SEM image of Comparative Example 1, with a scale of 400 nm. Fig. 9 (b) is the SEM image of Example 2, and the scale bar is 400 nm;
[0040] Fig.10 is a schematic diagram comparing the electrical properties of the tin oxide electron transport layer prepared in Comparative Example 1 and Example 2 of the present invention, wherein: Fig.10 (a) is the conductivity diagram, Fig.10 (b) is the electron mobility diagram;
[0041] Fig.11 is a contact angle diagram of the tin oxide electron transport layer prepared in Comparative Example 1 and Example 2 of the present invention, wherein: Fig.11 (a) is the contact angle diagram of Comparative Example 1, Fig.11 (b) is the contact angle diagram of Example 2;
[0042] Fig.12 is a SEM image of the surface of the perovskite light-absorbing layer prepared in Comparative Example 1 and Example 2 of the present invention, wherein: Fig.12 (a) is the SEM image of Comparative Example 1, with a scale of 500 nm. Fig.12 (b) is the SEM image of Example 2, and the scale bar is 500 nm;
[0043] Fig.13 is a schematic diagram comparing the defect state density of the perovskite light absorbing layer prepared in Comparative Example 1 and Example 2 of the present invention, wherein: Fig.13 (a) is the defect state density diagram of comparative example 1, Fig.13 (b) is the defect state density diagram of Example 2;
[0044] Fig.14 It is a schematic diagram comparing the ultraviolet stability of the perovskite solar cells prepared in Comparative Example 1 and Example 2 of the present invention. DETAILED DESCRIPTION
[0045] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features or features mentioned in the specific examples mentioned in the present invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0046] Example 1
[0047] The present invention provides a cerium-doped tin oxide electron transport layer, and a preparation method thereof comprises the following steps:
[0048] S1: Clean the FTO substrate: Use detergent, deionized water, acetone, isopropanol, and anhydrous ethanol to ultrasonically clean once, each for 20 minutes. After cleaning and drying, perform UV-ozone treatment for 15 minutes or plasma treatment for 3 minutes to improve the hydrophilicity of the substrate surface. The FTO substrate specifications are 15mm×15mm×2.2mm.
[0049] S2: After measuring 200 mL of deionized water and freezing it to form an ice-water mixture, 2.500 g of urea, 2.5 mL of concentrated hydrochloric acid, 50 μL of thioglycolic acid and 0.550 g of stannous chloride dihydrate were slowly added to the ice-water mixture in sequence, and stirred until completely dissolved to obtain a tin oxide precursor solution.
[0050] S3, weighing 14.8 mg of cerium chloride and adding it to the tin oxide precursor solution obtained in S2 to obtain a tin oxide precursor solution containing cerium salt, wherein the concentration ratio of cerium ions to tin ions is 2.5%;
[0051] S4. Immerse the FTO substrate treated by S1 in the cerium salt-containing tin oxide precursor solution in S3, and then deposit it at a constant temperature of 90°C. After deposition for 3.5 hours, take out the substrate, use isopropanol for ultrasonic cleaning for 5 minutes, dry it, and anneal it at 180°C for 1 hour to finally obtain a cerium-doped tin oxide electron transport layer.
[0052] Figure 1 Schematic diagram of the structure of a normal perovskite solar cell containing a cerium-doped tin oxide electron transport layer according to the present invention. Figure 1 As shown, this embodiment provides a normal perovskite solar cell comprising the above-mentioned cerium-doped tin oxide electron transport layer, and the preparation method thereof comprises the following steps:
[0053] T1, annealing the cerium-doped tin oxide electron transport layer deposited on the surface of the FTO substrate on a heating table at a temperature of 180°C for 10 minutes, and after cooling to room temperature, treating with UV-ozone for 15 minutes or plasma for 3 minutes for standby use;
[0054] T2. Preparation of FA1-x MA x The perovskite light-absorbing layer of the PbI3 structure has the following specific steps:
[0055] T2.1: Dissolve 691.5 mg of lead iodide in 1 mL of a mixed solvent of N,N-dimethylformamide (DMF) and N,N-dimethyl sulfoxide (DMSO), and stir on a magnetic stirrer until completely dissolved to obtain a lead iodide solution; wherein the volume ratio of DMF to DMSO solvent is 9:1;
[0056] T2.2: Dissolve 90 mg of formamidinium iodide (FAI), 6.4 mg of methylammonium iodide (MAI), and 9 mg of methylammonium chloride (MACl) in 1 mL of isopropyl alcohol (IPA) solvent, and stir at room temperature until completely dissolved to obtain a mixed organic salt solution of FAI, MAI, and MACl;
[0057] T2.3: In a nitrogen atmosphere, 50 μL of the lead iodide solution obtained in T2.1 was spin-coated on the surface of the cerium-doped tin oxide electron transport layer; wherein the spin-coating speed was 1500 rpm, the spin-coating acceleration was 750 rpm / s, the spin-coating time was 35 s, and then annealed on a hot stage at 70°C for 60 s to obtain a lead iodide film;
[0058] T2.4: Under a nitrogen atmosphere, 80 μL of the mixed organic salt solution obtained in T2.2 was spin-coated on the lead iodide film; wherein, the spin-coating speed was 2000 rpm, the spin-coating acceleration was 2000 rpm / s, the spin-coating time was 35 s, and then quickly transferred to an environment with a relative humidity of 30% to 40% and annealed at 150°C for 15 min to prepare a perovskite light-absorbing layer with a thickness of 700 nm.
[0059] T3. Preparation of hole transport layer: first, 72.3 mg of 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) was dissolved in 1 mL of chlorobenzene (CB) solvent, and then 28.8 μL of 4-tert-butylpyridine (tBP) and 17.5 μL of lithium bis(trifluoromethanesulfonic acid) imide (LiTFSI) solution were added and mixed evenly to prepare a hole transport layer solution, wherein the solubility of the LiTFSI solution was 520 mg / mL, and the solvent was acetonitrile. Finally, the prepared hole transport layer solution was spin-coated on the surface of the passivation layer; wherein the spin coating speed was 2500 rpm, the spin coating acceleration was 1250 rpm / s, and the spin coating time was 40 s.
[0060] T5. Preparation of electrode layer: In high vacuum (less than 10 -4 In an environment of 2400 Pa, a silver electrode is deposited on the hole transport layer by thermal evaporation, wherein the thickness of the electrode layer is 100 nm.
[0061] Performance test: The perovskite solar cell prepared in this example was placed in AM 1.5G, 100mW cm -2 Test under lighting conditions such as Figure 2 As shown in Figure 2, the reverse sweep photoelectric conversion efficiency of the perovskite solar cell is 23.35%, with an open circuit voltage of 1.17 V and a short circuit current density of 25.01 mA cm -2 , the filling factor is 79.66%.
[0062] Example 2
[0063] Taking Example 1 as a reference, the difference from Example 1 is that the concentration ratio of cerium ions to tin ions in the tin oxide precursor solution containing cerium salt in S3 is 5%.
[0064] Performance test: The perovskite solar cell prepared in this example was placed in AM 1.5G, 100mW cm -2 Test under lighting conditions such as Figure 3 As shown in Figure 2, the reverse sweep photoelectric conversion efficiency of the perovskite solar cell is 24.19%, with an open circuit voltage of 1.17 V and a short circuit current density of 25.31 mA cm -2 , the filling factor is 81.98%.
[0065] Example 3
[0066] Taking Example 1 as a reference, the difference from Example 1 is that the concentration ratio of cerium ions to tin ions in the tin oxide precursor solution containing cerium salt in S3 is 10%.
[0067] Performance test: The perovskite solar cell prepared in this example was placed in AM 1.5G, 100mW cm -2 Test under lighting conditions such as Figure 4 As shown in Figure 2, the reverse sweep photoelectric conversion efficiency of the perovskite solar cell is 22.84%, with an open circuit voltage of 1.15 V and a short circuit current density of 24.31 mA cm -2 , the filling factor is 81.66%.
[0068] Comparative Example 1
[0069] Taking Example 1 as a benchmark, the difference from Example 1 is that there is no S3 step, that is, no cerium salt is added to the tin oxide precursor solution, and a tin oxide electron transport layer and a perovskite solar cell without cerium doping are prepared.
[0070] Performance test: The perovskite solar cell prepared in comparative example 1 was placed in AM 1.5G, 100mW cm -2 Test under lighting conditions such as Figure 5As shown in Figure 2, the reverse sweep photoelectric conversion efficiency of the perovskite solar cell is 21.34%, with an open circuit voltage of 1.13 V and a short circuit current density of 23.40 mA cm -2 , the filling factor is 80.54%.
[0071] Figure 6 FIG. 1 is a schematic diagram comparing the JV curves of the perovskite solar cells in Comparative Example 1 and Example 2 of the present invention under AM 1.5G test conditions. Figure 6 As shown, the photoelectric conversion efficiency of perovskite solar cells prepared based on cerium-doped tin oxide electron transport layer was significantly improved from the initial 21.34% to 24.19%.
[0072] Figure 7 is a high-resolution energy spectrum of the tin oxide electron transport layer O1s prepared in Comparative Example 1 and Example 2 of the present invention, such as Figure 7 As shown, by vacant oxygen (V O ) peak area, compared with the non-cerium-doped tin oxide electron transport layer, the vacancy oxygen (V O ) is reduced, indicating that the defect states such as oxygen vacancies on its surface are significantly suppressed, which is beneficial to the extraction and transmission of photogenerated carriers.
[0073] Figure 8 is a high-resolution energy spectrum of the tin oxide electron transport layer Ce3d prepared in Comparative Example 1 and Example 2 of the present invention; Figure 8 As shown, by performing Ce element analysis on the surface of the tin oxide electron transport layer prepared in Example 2 and Comparative Example 1, Ce element signals are present on the surface of the tin oxide electron transport layer prepared in Example 2, indicating that cerium ions are present on the surface of the tin oxide electron transport layer.
[0074] Fig. 9 : is a SEM image of the cross section of the tin oxide electron transport layer prepared in Comparative Example 1 and Example 2 of the present invention; Fig. 9 (a) and Fig. 9 As shown in (b), the surface of the tin oxide electron transport layer prepared in Example 2 is smoother.
[0075] Fig.10 Schematic diagram comparing the electrical properties of the tin oxide electron transport layer prepared in Comparative Example 1 and Example 2 of the present invention; Fig.10 (a) is the conductivity diagram; Fig.10 (b) is the electron mobility diagram, which is given by Fig.10 It can be seen that the cerium-doped tin oxide electron transport layer has higher electrical conductivity and electron mobility, indicating that the cerium-doped tin oxide electron transport layer is more conducive to the transport of carriers.
[0076] Fig.11: is a contact angle diagram of the tin oxide electron transport layer prepared in Comparative Example 1 and Example 2 of the present invention; Fig.11 (a) and Fig.11 As shown in (b), compared with the tin oxide electron transport layer prepared in Comparative Example 1, the wetting contact angle of the cerium-doped tin oxide electron transport layer prepared in Example 2 is 32.5°, indicating that the wettability of the electron transport layer surface is further improved after doping with cerium, which is beneficial to the epitaxial growth of the perovskite light absorbing layer on the surface of the tin oxide electron transport layer.
[0077] Fig.12 is a SEM image of the surface of the perovskite light absorbing layer prepared in Comparative Example 1 and Example 2 of the present invention; Fig.12 (a) and Fig.12 As shown in (b), the perovskite light absorbing layer prepared on the surface of cerium-doped tin oxide electron transport layer has a larger average grain size and fewer holes, indicating that the perovskite light absorbing layer has a higher quality.
[0078] Fig.13 Schematic diagram comparing the defect state density of the perovskite light absorbing layer prepared in Comparative Example 1 and Example 2 of the present invention; Fig.13 (a) and Fig.13 As shown in (b), the perovskite light absorbing layer prepared on the surface of the cerium-doped tin oxide electron transport layer has a lower space charge limiting voltage (0.19 V), indicating that the prepared perovskite light absorbing layer has fewer defects.
[0079] Fig.14 FIG. 1 is a schematic diagram comparing the ultraviolet stability of the perovskite solar cells prepared in Comparative Example 1 and Example 2 of the present invention. Fig.14 As shown, the perovskite solar cell prepared based on the cerium-doped tin oxide electron transport layer maintained 77% of the initial efficiency under 260h of UV irradiation, indicating that the prepared perovskite solar cell has good UV resistance.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a cerium-doped tin oxide electron transport layer, characterized in that: The following steps are involved: S1, cleaning and drying the FTO substrate, and subjecting the surface of the FTO substrate to UV-ozone treatment for 5 to 20 minutes or plasma cleaning treatment for 1 to 5 minutes; S2, measuring deionized water and freezing it to form an ice-water mixture, and then slowly adding urea, concentrated hydrochloric acid, thioglycolic acid and stannous chloride dihydrate to the ice-water mixture in sequence, and stirring until completely dissolved to obtain a tin oxide precursor solution; S3, weighing a cerium salt and adding it to the tin oxide precursor solution obtained in S2 to obtain a tin oxide precursor solution containing a cerium salt; S4, immersing the FTO substrate treated by S1 into the tin oxide precursor solution containing cerium salt in S3, and depositing it under constant temperature conditions by a chemical bath method. After the deposition is completed, the substrate is taken out, and ultrasonic cleaning, drying, and annealing are performed in sequence to obtain a cerium-doped electron transport layer.
2. The method for preparing a cerium-doped tin oxide electron transport layer according to claim 1, characterized in that: In S2, the pH of the tin oxide precursor solution is 0.5-2.0, and the dosage of each component is 6.250-25.000 g / L of urea, 6.250-25.000 mL / L of concentrated hydrochloric acid, 125-500 μL / L of thioglycolic acid, and 1.375-5.500 g / L of stannous chloride dihydrate.
3. The method for preparing a cerium-doped tin oxide electron transport layer according to claim 1, characterized in that: In S3, the cerium salt is a combination of one or more cerium salts selected from cerium chloride, cerium phosphate, cerium nitrate and cerium acetate; and the concentration ratio of cerium ions to tin ions in the tin oxide precursor solution containing the cerium salt is 1% to 10%.
4. The method for preparing a cerium-doped tin oxide electron transport layer according to claim 1, characterized in that: In S4, the deposition temperature is 80-100° C., and the reaction time is 1-5 hours.
5. The method for preparing a cerium-doped tin oxide electron transport layer according to claim 1, characterized in that: In S4, the ultrasonic cleaning solution is one of ethanol, isopropanol, ethylene glycol, and propylene glycol, the ultrasonic cleaning time is 2 to 10 minutes, the annealing temperature is 140 to 200° C., the annealing time is 30 to 90 minutes, and the thickness of the cerium-doped electron transport layer is 10 to 100 nm.
6. An application of a cerium-doped tin oxide electron transport layer, characterized in that: The cerium-doped tin oxide electron transport layer prepared by the preparation method according to any one of claims 1 to 5 is applied to a perovskite solar cell, characterized in that it is applied to prepare an organic-inorganic hybrid normal perovskite solar cell with UV resistance, comprising the following steps: T1, preparing a cerium-doped tin oxide electron transport layer on the surface of the FTO substrate and subjecting it to UV-ozone treatment for 15 min or plasma cleaning treatment for 3 min; T2. Preparing a perovskite light-absorbing layer of APbX3 structure on the surface of the cerium-doped tin oxide electron transport layer, wherein A is one or more of methylammonium, formamidine, cesium ion, and potassium ion, and X is one or more of I, Br, and Cl; T3, directly preparing the hole transport layer on the surface of the perovskite light absorbing layer by spin coating; T4. Prepare an electrode layer on the surface of the hole transport layer by thermal evaporation or magnetron sputtering.
7. The use of a cerium-doped tin oxide electron transport layer according to claim 6, characterized in that: The material of the hole transport layer in T3 is 2,2',7,7'-tetrakis(4-methoxydiphenylamine)-9,9'-spirofluorene, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], nickel oxide, copper thiocyanate or copper iodide.
8. The use of a cerium-doped tin oxide electron transport layer according to claim 6, characterized in that: The electrode layer in T4 is one or more of gold, silver, copper, indium tin oxide, and aluminum-doped zinc oxide, and the thickness of the electrode is 50 to 300 nm.
Citation Information
Patent Citations
Inorganic inverted perovskite solar cell, and preparation method and application thereof
CN111430484A
Dopamine-doped perovskite solar cell and preparation method thereof
CN111540830A
N-chlorosuccinimide-doped tin dioxide electron transport layer, perovskite solar cell and preparation method of perovskite solar cell
CN116867342A
Perovskite battery based on acid-treated tin oxide and preparation thereof
WO2023124601A1
Method for manufacturing solar cell by doping perovskite bulk with sulfonyl molecules
WO2024098538A1
Cited By
Space perovskite battery and preparation method thereof
CN122396151A